Analysis of Sedimentary Environment Conditions for Lacustrine Fine-Grained Sedimentary Rocks and Its Control of Lithofacies Development: A Case Study of the Lower Submember of Member 3 of Shahejie Formation in FY-1 Well, Dongying Sag, Bohai Bay Basin, China. (13th September 2021) - Peng, Jun; Yu, Ledan; Xu, Tianyu; Wang, Yubin; Han, Haodong
Abstract : In recent years, the studies on fine-grained sedimentation mainly focus on the rock type, sedimentary environment, sedimentation, and sequence stratigraphy, while those on the relationship between sedimentary environment and lithofacies development are rare. However, a clear understanding on the relationship is of great significance to the muddy shale oil and gas exploration. This paper studied the muddy shale of semideep and deep lacustrine facies in the lower submember of Member 3 of Shahejie Formation in FY-1 Well, Dongying Sag, Bohai Bay Basin, East China. Based on geochemical data, the sedimentary environment media conditions and vertical changes of this submember were analyzed by means of core description, thin section authentication, X-ray diffraction (XRD), and other technologies, and the relationship between sedimentary environment and lithofacies development was discussed. The results show that this environment underwent three stages and is featured by cyclicity. From the bottom up, it experienced the semideep, deep, and deep/semideep waters under the relatively dry-cold/relatively warm-wet, warm-wet, and warm-wet/relatively warm-wet paleoclimates, respectively. Correspondingly, the paleoredox transited three stages from reducibility to high reducibility to high reducibility/reducibility; the paleosalinity changed from saline water to brackish water to brackish/saline water. Paleoproductivity was low/relatively high at the beginning, then became high, and finally relatively high. In this submember, the lithofacies primarily includes organic-rich mudstone, organic-rich lime mudstone, organic-rich lime-bearing mudstone, and organic-contained argillaceous limestone/lime mudstone. The sedimentary environment controls the mineral composition and content in the lithofacies and thus determines the lithofacies types. Meanwhile, the cyclicity of environmental change not only leads to that of the lithofacies development but also affects the positions of the lithofacies and its assemblages in sequence stratigraphic framework.